Genetically Modified Foods and Consumer Perspective - Boccia, Flavio; Sarnacchiaro, Pasquale (Recent Patents on Food, Nutrition & Agriculture, 2015)
Genetically modified food is able to oppose the world’s hunger and preserve the environment, even if the patents in this matter are symptomatic of several doubts. And also, transgenic consumption causes problems and skepticism among consumers in several European countries, but above all in Italy, where there is a strong opposition over recent years. So, the present study conducted a research to study the consumption of genetically modified food products by Italian young generation. This research presented the following purposes: firstly, to analyze genetically modified products’ consumption among a particular category of consumers; secondly, to implement a quantitative model to understand behaviour about this particular kind of consumption and identify the factors that determine their purchase. The proposed model shows that transgenic consumption is especially linked to knowledge and impact on environment and mankind’s health.
Keywords: Behaviour